2005
DOI: 10.1534/genetics.105.042002
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Mutation in Lines ofArabidopsis thalianaExposed to Ultraviolet-B Radiation

Abstract: Studies that have attempted to estimate the rate of deleterious mutation have typically been conducted under low levels of ultraviolet-B (UV-B) radiation, a naturally occurring mutagen. We conducted experiments to test whether the inclusion of natural levels of UV-B radiation in mutation-accumulation (MA) experiments influences the rate and effects of mildly deleterious mutation in the plant Arabidopsis thaliana. Ten generations of MA proved insufficient to observe significant changes in means or among-line va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 54 publications
(41 reference statements)
4
26
1
2
Order By: Relevance
“…These findings were true for traits that are direct components of fitness, such as fruit production and survival. Similar results have been found previously for these mutation accumulation lines (Roles et al., 2016; Rutter et al., 2010; Shaw et al., 2002) and independently derived MA lines from the same founder (MacKenzie et al., 2005). In total, these studies represent a collection of nine assays of lines derived from this founder: six in the field (across two sites and four seasons) and three in greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…These findings were true for traits that are direct components of fitness, such as fruit production and survival. Similar results have been found previously for these mutation accumulation lines (Roles et al., 2016; Rutter et al., 2010; Shaw et al., 2002) and independently derived MA lines from the same founder (MacKenzie et al., 2005). In total, these studies represent a collection of nine assays of lines derived from this founder: six in the field (across two sites and four seasons) and three in greenhouse conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Significant mutant line effects suggest that measured differences in these traits were due to induced mutations. These results are consistent with the notion that most mutations are deleterious (Keightley & Lynch, 2003) but conflict with recent results in studies of A. thaliana mutant lines (MacKenzie et al., 2005; Rutter et al., 2010; Shaw et al., 2000). …”
Section: Discussionmentioning
confidence: 99%
“…Earlier work on A. thaliana mutation accumulation lines, as well as on mutation accumulation lines from other species, has demonstrated that mutations can be beneficial more often than previously believed (Hall & Joseph, 2010; MacKenzie et al., 2005; Rutter et al., 2010; Shaw et al., 2000). In A. thaliana , mutation accumulation lines have been shown to have increased fitness over the premutation founder as much as 1/3 to 1/2 the time (MacKenzie et al., 2005; Rutter et al., 2010; Shaw et al., 2000), corresponding to high beneficial mutation rates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations